Analisis Pedagogi Digital Dalam Pembelajaran Istima’ Bahasa Arab: Optimalisasi Peran Video Animasi Untuk Meningkatkan Keterlibatan Dan Pemahaman Siswa Madrasah - Diana Azza, Zukhrufa; Aliwafa, Aliwafa (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to analyze the implementation of digital pedagogy in teaching the Arabic listening skill (maharah istima’) through the use of animated videos, as well as to measure its effectiveness in improving students’ engagement and comprehension in the madrasah context. This research employed a descriptive qualitative approach supported by quantitative data to strengthen the field findings. The data sources included Arabic language teachers, eighth-grade students, and instructional documents. Data collection techniques consisted of structured observations, in-depth interviews, documentation, and formative assessments in the form of simple pre-tests and post-tests to measure improvements in listening comprehension. Data analysis was carried out through data reduction, data display, and conclusion drawing, while data verification was conducted using source and technique triangulation. The results indicate that the use of animated videos successfully enhanced students’ motivation, attention, and participation in listening activities. Quantitative findings show a significant increase in the average listening comprehension score, from 71.25 on the pre-test to 91.87 on the post-test, reinforcing the qualitative results that animation helps students understand vocabulary, sentence structures, and conversational contexts more concretely. The teacher served as a digital facilitator guiding students through the pre-listening, while-listening, and post-listening stages. Overall, the integration of animated videos proved effective in supporting digital-pedagogy–based listening instruction and is highly relevant for wider implementation in madrasah settings.